Music Characteristics and Regional Differences in (SHE) Ethnic Minority Folk Songs: A Comparative Analysis of Ningde and Eastern Fujian Regions - Song , Lu-lu (Journal of Ecohumanism, 2024)
Tucked away in the stunning province of Fujian in southeast China, the region has a cultural tapestry as varied and vibrant as its breath-taking scenery. Through the analysis and coding of folk songs from four different geographical regions in China (Fujian and Ningde), this paper aimed to determine the degree of mutual interaction and integration of the musical cultures of the Shen and Han nationalities into modernity. It did this by developing a new musical characteristic density map for machine music classification. The nationality known as (SHE) is a small ethnic group in the area. The traditional cultural heritage as well as the growth of the (SHE) nationality have lagged behind the rapid advancement of modern times. This study investigates how to incorporate the culture of the (SHE) nationality into modern culture in order to fully realise the goal of "going out," starting from the conventional cultural heritage and creative growth of the (SHE) nationality. This paper discusses the formation of the (SHE) Minority folk songs in the context of protecting intangible cultural heritage. It does this by using the methods of literature research, field investigation, and comprehensive analysis to gather first-hand fresh field data from the components of historical evolution, protection process, inheritance method, development dilemma, and countermeasures. Questions of development and inheritance. The world will recognise the allure of the traditional culture of the (SHE) nationality as it is continuously enhanced and vibrant.